Facile synthesis of multicolor tunable ultrasmall LiYF4:Yb, Tm, Er/LiGdF4 core/shell upconversion nanophosphors with sub-10 nm size. (April 2017) - Hong, A-Ra; Kim, Su Yeon; Cho, So-Hye; Lee, Kwangyeol; Jang, Ho Seong
Abstract: Sub-10 nm-sized LiYF4 :Yb, Tm/Er upconversion nanophosphors (UCNPs) and multicolor-emitting LiYF4 :Yb, Tm, Er/LiGdF4 core/shell (C/S) UCNPs were facilely synthesized by using rare earth-oleate (RE(oleate)3 ) precursors. The size of LiYF4 :Yb, Tm and LiYF4 :Yb, Er UCNPs with single tetragonal phase was controlled in the range of 3.2–9.6 nm and 3.0–9.0 nm, respectivley, by varying reaction temperature from 230 to 320 °C under the use of RE(oleate)3 precursors. The sub-10 nm-sized LiYF4 :Yb(25%), Tm(0.5%)/LiGdF4 (9.7 nm) and LiYF4 :Yb(18%), Er(2%)/LiGdF4 (9.5 nm) C/S UCNPs were successfully synthesized from ultrasmall LiYF4 -based UCNP cores smaller than 5 nm in size. The blue- and green-emitting sub-10 nm-sized LiYF4 :Yb, Tm/LiGdF4 and LiYF4 :Yb, Er/LiGdF4 C/S UCNPs exhibited 566 and 48, 245 times higher upconversion luminescence intensities than their core counterparts, respectivley, under excitation with 980 nm near infrared light. In addition, multicolor tunable sub-10 nm-sized LiYF4 :Yb, Tm, Er/LiGdF4 C/S UCNPs were synthesized and they emitted bright blue, sky blue, aquamarine, and green light by varying dopant composition (Tm and Er) and concentration. Graphical abstract: